America's religious history: faith, politics, and the shaping of a nation - Kidd, Thomas S. (Zondervan Academic, 2019)
Religion in early America -- Reviving American faith -- Religion and the American Revolution -- The era of the Second Great Awakening -- Global and domestic missions -- Slave religion and manifest destiny -- The slavery controversy and the Civil War -- Immigration and religious diversity -- Evolution, biblical criticism, and fundamentalism -- The religious challenges of the world wars -- Civil religion and the Cold War -- Civil rights and church-state controversy -- The Christian right and the changing face of American religion -- Immigration, religious diversity, and the culture wars -- Epilogue: American religion in the twenty-first century.